An Historical Geography of Tourism in Victoria, Australia Case Studies - Clark, Ian (De Gruyter, 2014)
A Historical Geography of Tourism in Victoria, Australia - Case studies is concerned with the emergence of tourism in colonial Victoria, Australia. It explores a fundamental set of questions: how does a tourist site come in to being? How does a tourist gaze emerge in a 'settler society'? How does an 'era of discovery' segue into 'tourism'? And, how was the tourist map of Victoria created by settler colonists? Through the application of the classical models of MacCannell, Butler, and Gunn to construct the history of tourism at eight case studies, this work shows that Victoria's tourism landscape is dynamic and constantly changing. There are many other significant natural and cultural attractions in Victoria and much more research needs to be undertaken to understand more fully the evolution of Victoria's tourism landscape.